Non-teratoid ocular medulloepithelioma in an adult horse - Mariana Oliveira Silva; Leonardo Costa Tavares Coelho; Adriane Pereira Vidal; Cíntia Alves Teixeira; Gustavo Henrique Siqueira Ribeiro; Natália Cristina de Melo; Priscila Fantini (Ciência Rural, 2021)
ABSTRACT: This is a case of medulloepithelioma in a 14-year-old mixed breed gelding horse, presenting a large abnormal mass of tissue involving the entire extension of the right eye. Ophthalmic examination showed deformation and swelling of the eye. The animal showed signs of pain on palpation of the organ, but the specific examination of the systems did not reveal any other changes. Due to the extension of the apparently neoplastic mass and the discomfort experienced by the animal, transpalpebral enucleation procedure was decided. The excised tissue was sent for histopathological analysis, wherein a neoplastic proliferation of neuroectodermal cells was noted. The neoplasm was poorly delimited, unencapsulated, infiltrative, sustained by moderate fibrovascular stroma, and formed cords and rosettes with cells arranged in palisades around the luminal structures (Flexner-Wintersteiner rosettes), suggestive of medulloepithelioma. The immunohistochemical profile was also performed, confirming the diagnosis. The neoplastic cells were immunolabeled to vimentin, S100 protein (S100), and specific neuro enolase (NSE), but not for pan cytokeratin (AE1AE3), glial fibrillary acidic protein (GFAP), and cytokeratin 8/18 (CK8/18). Five months postoperatively, the animal was healthy, without any relapse or evidence of metastasis.